Control of perpendicular magnetic anisotropy and spin pumping damping in MgO/CoFeB/ Ta/Pt structures. (9th August 2017) - Zhu, Zhendong; Chen, Shaohai; Zhao, Bingcheng; Jin, Q Y; Chen, Jingsheng; Zhang, Zongzhi
Abstract: The perpendicular magnetic anisotropy (PMA) and spin pumping induced magnetic damping of CoFeB films can be significantly tuned by the adjacent nonmagnetic layer (Ta or Pt). For the CoFeB/Pt( t Pt ) structure, both PMA strength and magnetic damping increase with t Pt, due to the enhanced interfacial orbital hybridization and spin pumping effects, respectively. By inserting a thin Ta interlayer between CoFeB and Pt, the magnetic easy axis immediately turns into in-plane direction. Meanwhile, time-resolved magneto-optical Kerr effect measurement shows an obvious reduction in the magnetic damping, which can be explained as the increase of spin current backflow and the decrease of interfacial spin-mixing conductivity. As the Ta interlayer thickness ( t Ta ) increases, the effective damping parameter α s measured at saturation field initially decreases and eventually reaches a constant value of 0.027. The α s value at t Ta > 5 nm does not change regardless of the top Pt layer, implying the influence of Pt is completely isolated and the spin diffusion length of Ta is around 5 nm. Our findings provide more insights into the control of PMA strength and spin pumping contribution to magnetic damping.